Study of the Effect of Terminalia Chebula Seed Extract on Inhibiting the Growth of Bacteria Isolated From Urinary Tract Infection - Ali, Gunay Abdulrahman; Sabah, Sarah Muneeb; Mahmood , Ihab Shihab Ahmed; Hamd, Yuosf Hussin; Jafar, Nehan Bahaaldden (American Journal of Biology and Natural Sciences, 2025)
Herbal medications make up a significant portion of all accepted health systems worldwide. Additionally, medicinal plants are thought to be inexpensive and valuable sources of a variety of phytoconstituents that are often used in the creation of medications to treat a wide range of illnesses. 140 urine samples were collected between July and September 2024 from UTI-afflicted women who were sent to the laboratory after seeing a specialist and being admitted to Azadi Teaching Hospital in Kirkuk City. Following identification of the bacterial colonies on blood agar based on their culture properties, they were incubated at 37 0C for 24 hours. The data indicated that when cultivated in the optimal culture medium, 109 (77.9%) of the total samples demonstrated favorable results for bacterial growth. Thirty-one (22.1%) of the total samples had negative results for bacterial growth. With 51 (46.7%) isolates, E. coli had the highest incidence of urinary tract infections. S. aureus (20.2%), P. mirabilis (12.0%), P. aeruginosa (8.3%), and K. pneumonia (16.7%) were next in line. E. coli, K. pneumonia, and P. aeruginosa all shown high resistance to ampicillin, making it the antibiotic most resistant to all bacterial taxa in the research. All of the bacteria under study, however, shown a significant susceptibility to tobramycin, amikacin, and ezetrenam. Additionally, the results demonstrated T. chebula's capacity to suppress bacteria based on concentration. The isolates of E. coli, P. mirabilis, K. pneumonia, P. aeruginosa, and S. aureus were inhibited by 50, 100, and 150 ul of T. chebula. E. coli was the most sensitive to the extract, with an average diameter of inhibition of 29.2±4.2, while S. aureus was the least sensitive, with an average diameter of inhibition of 19.5±3.5. The highest effective concentration for inhibiting bacterial growth was determined to be 150ul. T. chebula seed extract was found to exhibit antibacterial activity against both Gram-positive and Gram-negative bacteria.